Prospectus. - Braem, Philippe; De Bontridder, Yolande; de Bellefroid, Véronique; la Communauté Française de Belgique, Bruxelles; De Vlaamse Gemeenschapscommissie (Brussel : Prospectus Brussel, 1994)
't Jolle, Sven ; Barry, Orla ; Berlanger, Marcel ; Bird, Terri ; De Bruyn, Goele ; Claus, Thomas ; Closset, Brigitte ; Degrève, Mia ; Draeger, Christoph ; Felix, Benoît ; Fink, Christoph ; Henderick, Bénédicte ; Janssens de Bisthoven, Sylvie ; Meeussen, Veerle ; Moens, Rik ; Nölle, Annick ; Thompson, Jon ; Vandenabeele, Lukas ; Vanderleenen, Marc ; Vanpevenaege, Yves ; Wichers, Patries
mapje met 26 losse kaarten
Frans
Nederlands
Prospectus, Brussel, 06.05 - 25.06.1994
boek